Periodicity and transversal pressure distribution in a Wire‐wrapped 19‐Pin fuel assembly. (4th September 2020) - Fan, Dajun; Peng, Tianji; Tang, Yanze; Zhao, Qiang; Tian, Wangsheng; Liu, Daxiao; Li, Rongjie; Wang, Dawei; Gu, Long
Summary: An experimental setup was designed and constructed to investigate the detailed pressure distribution data of a wire‐wrapped fuel assembly and to evaluate the friction factor correlations. The test section was a wire‐wrapped 19‐pin fuel assembly manufactured with polymethyl methacrylate, and the working liquid was deionized water. A secondary circuit supplying chilled water was built to minimize the changes in the physical properties of the working liquid induced by temperature fluctuation. Eighteen axial differential pressure drops and twelve transversal differential pressure drops with Reynolds number in the range of 3750 to 16 250 were measured. The relation between the friction factor and Reynolds number was analyzed. The results showed that the axial pressure in the edge subchannels varied periodically similar to a helical pitch. The direction of rotation and height of the wire‐wrap spacers in the subchannels have a significant effect on the transversal pressure distribution, especially in the zones where the wire‐wrap spacers cross. Besides, the Rehme correlation and Cheng and Todreas Detailed (CTD) correlation showed the best fit with the experimental data. The critical Reynolds number, where the shift from the transitional to turbulent flow regions occurs, is approximately 11 700, and the difference between the experimental data and the value predicted by the CTD correlation was approximately 8.33%. The experimental data of the pressure distribution in the wire‐wrapped fuel assembly could complement the existing database, which supports the development of fast reactors. Abstract :